2015
DOI: 10.1096/fj.15-276857
|View full text |Cite
|
Sign up to set email alerts
|

High‐intensity sprint training inhibits mitochondrial respiration through aconitase inactivation

Abstract: Intense exercise training is a powerful stimulus that activates mitochondrial biogenesis pathways and thus increases mitochondrial density and oxidative capacity. Moderate levels of reactive oxygen species (ROS) during exercise are considered vital in the adaptive response, but high ROS production is a serious threat to cellular homeostasis. Although biochemical markers of the transition from adaptive to maladaptive ROS stress are lacking, it is likely mediated by redox sensitive enzymes involved in oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 35 publications
5
79
0
Order By: Relevance
“…The general effects of the interventions are reported with more detail in previous publications . Briefly, in the overweight walking group, the combination of caloric restriction with prolonged exercise elicited an energy deficit of 5500 kcal/day .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The general effects of the interventions are reported with more detail in previous publications . Briefly, in the overweight walking group, the combination of caloric restriction with prolonged exercise elicited an energy deficit of 5500 kcal/day .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast with rodent data, here we have demonstrated that a short training program based on repeated high‐intensity exercise reduced the SLN protein levels in vastus lateralis despite eliciting much less total energy expenditure than the 4‐day walking intervention. A principal difference between prolonged walking and repeated 30‐second all‐out sprints is the marked metabolic disturbances evoked by the sprints, which cause substantial lactic acidosis, oxidative stress, and sarcoplasmic reticulum stress . Endoplasmic reticulum stress reduces SLN expression in C2C12 cells .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, aconitase activity is widely used as a biomarker for oxidative stress, as high-intensity exercises in humans lead to inactivation of aconitase due to ROS generation [19, 21-23]. These indicated that functional aconitase was essential in maintaining redox balance and the cellular antioxidant defense system [22]. Therefore, we inferred that deficiency of NARFL promoted production of ROS, either directly [13] or via decreased aconitase activity, resulted in iron overload [19-25].…”
Section: Discussionmentioning
confidence: 99%